1962
DOI: 10.1266/jjg.37.24
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Differentiation of Cultivated Rice, XX Analysis of the Genetic Basis of Hybrid Breakdown in Rice

Abstract: Distantly related varieties of cultivated rice (Oryza sativa L.) often show partial sterility in their F1 hybrids.The senior writer formerly demonstrated that this sterility could be accounted for by gametic-development genes, i.e., duplicate genes whose double recessive combinations interrupt the development of gametes carrying them (Oka 1953(Oka , 1957b. This hypothesis could plausibly explain segregation in certain ratios of fertile and partially sterile plants in experimental crosses, modification of F2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
1

Year Published

1962
1962
2008
2008

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 5 publications
4
25
0
1
Order By: Relevance
“…However, it is not easy to introduce genes with increasing effects on spikelet number per panicle from an indica variety into Japanese japonica varieties, since the hybrid sterility and hybrid lethality between indica and japonica cause reproductive isolation (Kato et al 1928, Terao and Midushima 1939, Oka 1954and 1957, Oka and Doida 1962. So, if a major gene known to increase spikelet number per panicle can enlarge sink size per unit area and is contained in a japonica variety or line, we could utilize it for developing high yielding japonica varieties.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not easy to introduce genes with increasing effects on spikelet number per panicle from an indica variety into Japanese japonica varieties, since the hybrid sterility and hybrid lethality between indica and japonica cause reproductive isolation (Kato et al 1928, Terao and Midushima 1939, Oka 1954and 1957, Oka and Doida 1962. So, if a major gene known to increase spikelet number per panicle can enlarge sink size per unit area and is contained in a japonica variety or line, we could utilize it for developing high yielding japonica varieties.…”
Section: Introductionmentioning
confidence: 99%
“…Many reports are available on the genetic analysis of hybrid breakdown in rice (Oka 1957, 1978, Oka and Doida 1962, Yokoo 1984, Sato and Morishima 1988, Wu et al 1995, Li et al 1997, Kubo and Yoshimura 2002, Fukuoka et al 2005, Yamamoto et al 2007, Matsubara et al 2007a, 2007b. These studies demonstrated that hybrid breakdown is induced by the interaction of two or three genes derived from each parent.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the associations found among the varietal sample were partly caused by natural or artificial selections at the zygotic stage. Random drift may not be a causal factor because indica-japonica differentiation was also obseved in African cultivers of 0. sativa that have been established apart from Asian cultivers for a long time (de Kochko, 1987 In indica x japonica crosses, partial sterility of hybrids is frequently observed (e.g., Oka, 1953Oka, , 1974Oka and Doida, 1962;Yokoo, 1984;Ikehashi and Araki, 1986) and results in gametic selection. Competition between pollen grains during pollen tube elongation which is caused by particular genes also results in gametic selection.…”
Section: Discussionmentioning
confidence: 99%